Characteristics of the transverse 2D uniserial arrangement of rows of decussating enamel rods in the inner enamel layer of mouse mandibular incisors. Issue 5 (11th August 2019) - Smith, Charles E.; Hu, Yuanyuan; Hu, Jan C‐C.; Simmer, James P.
Abstract: The 2D arrangement of rows of enamel rods with alternating (decussating) tilt angles across the thickness of the inner layer in rat and mouse incisor enamel is well known and assumed to occur in a uniform and repetitive pattern. Some irregularities in the arrangement of rows have been reported, but no detailed investigation of row structure across the entire inner enamel layer currently exists. This investigation was undertaken to determine if the global row pattern in mouse mandibular incisor enamel is predominately regular in nature with only occasional anomalies or if rows of enamel rods have more spatial complexity than previously suspected. The data from this investigation indicate that rows of enamel rods are highly variable in length and have complex transverse arrangements across the width and thickness of the inner enamel layer. The majority of rows are short or medium in length, with 87% having < 100 rods per row. The remaining 13% are long rows (with 100–233 rods per row) that contain 46% of all enamel rods seen in transverse sections. Variable numbers of rows were associated with the lateral, central and mesial regions of the enamel layer. Each region contained different ratios of short, medium and long rows. A variety of relationships was found along the transverse length of rows in each region, including uniform associations of alternating rod tilts between neighboring rows, and instances where two rows having the same rod tilt were paired for variable distances then moved apart to accommodate rows of opposite tilt. Sometimes a row appeared to branch into two rows with the same tilt, or conversely where two rows merged into one row depending upon the mesial‐to‐lateral direction in which the row was viewed. Some rows showed both pairing and branching/merging along their length. These tended to be among the longest rows identified, and they often crossed the central region with extensions into the lateral and mesial regions. The most frequent row arrangement was a row of petite length nestled at the side of another row having the same rod tilt (30% of all rows). These were termed 'focal stacks' and may relate to the evolution of uniserial rat and mouse incisor enamel from a multilayered ancestor. The mesial and lateral endpoints of rows also showed complex arrangements with the dentinoenamel junction (DEJ), the inner enamel layer itself, and the boundary area to the outer enamel layer. It was concluded that the diversity in row lengths and various spatial arrangements both within and between rows across the transverse plane provides a method to interlock the enamel layer across each region and keep the enamel layer compact relative to the curving DEJ surface. The uniserial pattern for rows in mouse mandibular incisors is not uniform, but diverse and very complex. Abstract : Enamel rods in rodent incisors are arranged as stacked rows with alternating tilt angles across the transverse plane of the tooth. This study quantifies row patterns to determine if the layering of the rows and the alternating tilt angles are uniform or more irregular and complex in arrangement. The results indicated considerable diversity in row lengths, row tilts and 2D spatial row arrangements both within and between rows.